2015
DOI: 10.1016/j.csl.2014.10.003
|View full text |Cite
|
Sign up to set email alerts
|

A generalised alignment template formalism and its application to the inference of shallow-transfer machine translation rules from scarce bilingual corpora

Abstract: Statistical and rule-based methods are complementary approaches to machine translation (MT) that have different strengths and weaknesses. This complementarity has, over the last few years, resulted in the consolidation of a growing interest in hybrid systems that combine both data-driven and linguistic approaches. In this paper we address the situation in which the amount of bilingual resources that is available for a particular language pair is not sufficiently large to train a competitive statistical MT syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 24 publications
0
15
0
Order By: Relevance
“…Tyers, Sánchez‐Martínez, and Forcada () used statistical lexical semantics to disambiguate translation inputs in the source. Sánchez‐Cartagena, Pérez‐Ortiz, and Sánchez‐Martínez () generated transfer rules (without probabilities) from a parallel corpus. These rules can then be used in combination with manually written transfer rules, if available (Costa‐jussà & Centelles, in press).…”
Section: Hybrid Rule‐based and Statistical Mt Architecturesmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyers, Sánchez‐Martínez, and Forcada () used statistical lexical semantics to disambiguate translation inputs in the source. Sánchez‐Cartagena, Pérez‐Ortiz, and Sánchez‐Martínez () generated transfer rules (without probabilities) from a parallel corpus. These rules can then be used in combination with manually written transfer rules, if available (Costa‐jussà & Centelles, in press).…”
Section: Hybrid Rule‐based and Statistical Mt Architecturesmentioning
confidence: 99%
“…When it comes to increasing the amount of hybridization, there are some cases where adding linguistic knowledge penalizes the statistical MT system, for example, as proven by limiting translation units (Koehn et al, 2003) or reordering with linguistic criteria (Costa-jussà et al, 2007). Likewise, in the case of rule-based MT, using statistical data can be harmful, as it has been observed that in general manual transfer rules still achieve better results compared to the automatically extracted ones (Sánchez-Cartagena et al, 2015).…”
Section: Complexity Versus Improvementmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the translation into TL is generated from the TL lexical forms: J'aime la maison de Pierre. 3.2 A rule formalism suitable for rule inference Figure 1 shows the second rule applied in the example from the previous section encoded with the formalism we have defined for rule inference (Sánchez-Cartagena et al, 2014). Each rule contains a sequence of SL word classes (depicted as the sequence of boxes at the top of the figure) and TL word classes (the sequence of boxes below them).…”
Section: Related Workmentioning
confidence: 99%
“…They are a subset of the steps followed by Sánchez-Cartagena et al (2014) to infer shallow-transfer rules to be used in Apertium from small parallel corpora.…”
Section: Rule Inference Algorithmmentioning
confidence: 99%